Deformation and mechanical characteristics of tunneling in squeezing ground: A case study of the west section of the Tawarazaka Tunnel in Japan. (March 2021) - Wang, Xiaoshan; Iura, Tomomi; Jiang, Yujing; Wang, Zaiquan; Liu, Richeng
Highlights: Ground squeezing is prone to occur in geologic unites with Paleogene mudstones. A lager value of initial horizontal stress ratio K0 leads to a greater convergence ratio λ . Ground squeezing is mainly affected by the moduli of rocks nearby. The convergence ratio tends to stabilize when a critical overburden depth is exceeded. Abstract: Ground squeezing induced by tunnel excavation is a common phenomenon in weak and jointed rock masses. The prediction of convergence during tunnel construction in squeezing ground is important for the selection of temporary support and excavation methods. In the present study, the main factors that lead to ground squeezing are discussed based on a case study of the west section (WS) of the Tawarazaka Tunnel. A systematic analysis of convergences measured on site is presented, and numerical modeling using the finite difference method (FDM) is performed. The results show that ground squeezing is prone to occur in Paleogene mudstone formations, especially when slickensides are strongly developed. Ground squeezing is affected by the initial horizontal stress ratio, and a larger initial horizontal stress ratio lead to a larger convergence ratio, which is defined as the ratio of horizontal convergence to vertical convergence. Tunnel convergence values linearly increase with the decrement of bedding joint stiffness, and tunnel convergence increases with the increment of internal friction angle of bedding joints. Ground squeezing in the WS is mainly affected by the modulus values of nearby rocks and the existence of bedding joints. For the WS of the Tawarazaka Tunnel, the convergence ratio tends to stabilize when a critical overburden depth of 100 m is exceeded.